Patient satisfaction with the dental services offered by a dental Hospital in India - N Nagappan; Joseph John (Wolters Kluwer Medknow Publications, 2014)
Introduction: A major component of quality of health care is patient satisfaction. Patient satisfaction is multifaceted and a very challenging outcome to define. Patient expectations of care and attitudes greatly contribute to the satisfaction; other psychosocial factors, including facilities and treatments services are also known to contribute to patient satisfaction scores. Aim: To measure patient satisfaction about facilities, services and treatments offered by a dental hospital in India. Materials and Methods: Self administrated questionnaire was distributed to outpatients reporting to the dental hospital for treatment. The questionnaire consisted of 30 items that included information about personal data of the patients and their satisfaction with the facilities, services and treatment received in the hospital. Results: About 89.9% of patients felt that the cost of dental hygiene services were reasonable, 57.6% of patients felt that drinking water facilities were enough in the hospital, 31.9% of patients felt that they have problem with scheduling appointments, 86% of patients felt that they had problem in contacting student dentist. Conclusion: The majority of the patients were satisfied with the facilities, services and treatment received at hospital except for facilities such as water supply and scheduling appointments with patient convenience.